PENGARUH STRUKTUR KEPEMILIKAN, LEVERAGE, UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2017 - Dwi Febrianti; Yolandafitri Zulvia (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2020)
The purpose of this study is to determine the factors that influence dividend policy on Manufacturing companies listed on the Indonesia Stock Exchange. These factors include Managerial Ownership (KM), Institutional Ownership (KI), Foreign Ownership (KA), Leverage (DER), Company Size (SIZE). This type of research is causative and quantitative and the data used are secondary data. Sampling in this study used a purposive sampling method, so that the manufacturing companies sampled amounted to 63 companies. Data analysis methods used are Descriptive Analysis, Classical Assumption Test, Multiple Linear Regression Analysis, and Model Feasibility Test. The results show that Managerial Ownership, Institutional Ownership, Foreign Ownership have no effect on Dividend Policy. While Leverage and Company Size have a significant influence on Dividend Policy.